2019
DOI: 10.1016/j.funbio.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A host specialized form of Ceratocystis fimbriata causes seed and seedling blight on native Carapa guianensis (andiroba) in Amazonian rainforests

Abstract: a b s t r a c tCeratocystis fimbriata Ellis & Halsted recently was recorded causing seed and seedling blight on Carapa guianensis Aubl. (andiroba), a tree species native to the Amazon Rainforest and prized for its valuable timber and medicinal seed oil. C. fimbriata more commonly causes wilt type diseases in woody hosts, especially on non-native host trees. However, on andiroba the disease occurs on seedlings and seeds, affecting the species regeneration. We studied 73 isolates of C. fimbriata on andiroba from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…This is also consistent with recent molecular genetic data showing that isolates of C. fimbriata from sweet potato represent a clonal lineage ( Li et al . 2016 ), which has also been designated ( Valdetaro et al . 2019 ) as a host-specific form referred to as C. fimbriata f. sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also consistent with recent molecular genetic data showing that isolates of C. fimbriata from sweet potato represent a clonal lineage ( Li et al . 2016 ), which has also been designated ( Valdetaro et al . 2019 ) as a host-specific form referred to as C. fimbriata f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate the phylogenetic relationship between the sweet potato isolate of C. fimbriata epitypified in this paper, other sweet potato isolates and forma specialis ( Valdetaro et al . 2019 ) available in GenBank, and closely related species ( Fourie et al 2015 , Marin-Felix et al 2017 ) a phylogenetic tree was constructed based on the ITS gene regions using maximum parsimony analysis as described in Fourie et al (2015) .…”
Section: Methodsmentioning
confidence: 99%
“…The name C. fimbriata f. sp. ipomoea was proposed for this strain (Valdetaro et al 2019), however, Marincowitz et al (2020) who have recently designated an epitype for C. fimbriata, treat this name as a synonym of C. fimbriata sensu stricto. This study has shown that the New Zealand kūmara isolates of C. fimbriata are not pathogenic on the kiwifruit cultivars tested, and there is unlikely to be a threat from the New Zealand Ipomoea strain moving into kiwifruit orchards.…”
Section: Discussionmentioning
confidence: 99%
“…; Tarigan et al, 2011), rubber tree (Hevea sp. ; Valdetaro et al, 2015), and andiroba (Carapa guianensis; Valdetaro et al, 2019).…”
mentioning
confidence: 99%
“…Some species have been described mainly based on variation of the internal transcribed spacer (ITS) region, revealing some taxonomic problems (Harrington et al, 2014). On the other hand, a biological species concept considering phenotype and mating studies has been applied to the C. fimbriata complex (Ferreira et al, 2010;Oliveira et al, 2015;Valdetaro et al, 2019). Efforts have been made to identify accurate methodologies for a better clarification of species differentiation and, therefore, provide a better understanding of the biology and ecology of this important group of fungi.…”
mentioning
confidence: 99%